2008
DOI: 10.1097/brs.0b013e31815e39af
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Study of Postoperative Lumbar Epidural Hematoma

Abstract: Lumbar decompression surgery results in a 58% incidence of asymptomatic compressive postoperative epidural hematoma. Adjacent level compression by hematoma occurs in 28% of patients. Advanced age, multilevel procedures, and international normalized ratio are independently associated with postoperative hematoma volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
111
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(114 citation statements)
references
References 16 publications
2
111
1
Order By: Relevance
“…Until now it is not known, what are the differences in MRI between the patients requiring revision surgery for symptomatic epidural compression by hematoma in the early postoperative period and those with uneventful course, since mass effect in early postoperative MRI is a common finding and can be regarded as ''normal'' [6,7]. In the literature the correlation between clinical symptoms and radiological findings of early postoperative MRI is found to be low [5,7,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Until now it is not known, what are the differences in MRI between the patients requiring revision surgery for symptomatic epidural compression by hematoma in the early postoperative period and those with uneventful course, since mass effect in early postoperative MRI is a common finding and can be regarded as ''normal'' [6,7]. In the literature the correlation between clinical symptoms and radiological findings of early postoperative MRI is found to be low [5,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…The sparse literature on characteristics of MRI in the early postoperative period after decompression in lumbar spinal stenosis reported various rates of hematoma [8,9]. Only one study reported dimensions of hematoma and cross-sectional area (CSA) of dural sac pre-and postoperatively in patients with different surgical approaches [8,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Jackson described the first case of SEH in 1869 [3], several hundred cases with various etiologies and risk factors such as an age of older than 60 years, Rh-positive blood type, and multilevel procedures (more than five levels) have been reported [1,7,17]. Preoperative nonsteroidal anti-inflammatories use, hemoglobin less than 10 g/dL, and preoperative and postoperative coagulopathy were also identified as predisposing factors that can be prevented or corrected [1,7,17]. Although our patient had none of these risk factors, coagulopathy is a risk even in those without a history.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative spinal epidural hematoma (SEH) is not an uncommon condition; in asymptomatic patients, postoperative MRI and CT studies have identified postoperative SEH in 33% to 100% after lumbar disc or decompression surgery [6,15,17,20]. In contrast, the incidence of postoperative SEH that necessitates surgical decompression ranges from 0.1% to 3% [1,2,7,8].…”
Section: Introductionmentioning
confidence: 99%